Evaluation of cannabinoid type 2 receptor expression and pyridine-based radiotracers in brains from a mouse model of Alzheimer’s disease - Kecheliev, Vasil; Spinelli, Francesco; Herde, Adrienne; Haider, Achi; Mu, Linjing; Klohs, Jan; Ametamey, Simon M.; Ni, Ruiqing (Frontiers in Aging Neuroscience, 2022)
Neuroinflammation plays an important role in the pathophysiology of Alzheimer’s disease. The cannabinoid type 2 receptor(CB2R) is an emerging target for neuroinflammation and therapeutics of Alzheimer’s disease. Here, we aim to assess the alterations in brain CB2R levels and evaluate novel CB2R imaging tracers in the arcAb mouse model of Alzheimer’s disease amyloidosis. Immunohistochemical staining for amyloid-b deposits(6E10), microgliosis(anti-Iba1 and anti-CD68 antibodies), astrocytes(GFAP) and the anti-CB2R antibody was performed on brain slices from 17-month-old arcAb mice. Autoradiography using the CB2R imaging probes [18F]RoSMA-18-d6, [11C]RSR-056 and [11C]RS-028 and mRNA analysis were performed in brain tissue from arcAb and nontransgenic littermate (NTL) mice at 6, 17, and 24 months of age. Specific increased CB2R immunofluorescence intensities on the increased number of GFAP-positive astrocytes and Iba1-positive microglia were detected in the hippocampus and cortex of 17-month-old arcAb mice compared to NTL mice. CB2R immunofluorescence was higher in glial cells inside 6E10-positive amyloid-b deposits than peri-plaque glial cells, which showed low background immunofluorescence in the hippocampus and cortex of 17-month-old arcAb mice. Ex-vivo autoradiography showed that the specific binding of [18F]RoSMA-18-d6 and [11C]RSR-056 was comparable in arcAb and NTL mice at 6, 17, and 24 months of age. The level of Cnr2 mRNA expression in the brain was not significantly different between arcAb and NTL mice at 6, 17 or 24 months of age. In conclusion, we demonstrated pronounced specific increases in microglial and astroglial CB2R expression levels in mouse model of AD-related cerebral amyloidosis, emphasizing CB2R as a suitable target for imaging neuroinflammation.